2019
DOI: 10.3389/fphys.2019.00582
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Monitoring During Strength and High-Intensity Interval Training Overload Microcycles

Abstract: Objective: In two independent study arms, we determine the effects of strength training (ST) and high-intensity interval training (HIIT) overload on cardiac autonomic modulation by measuring heart rate (HR) and vagal heart rate variability (HRV). Methods: In the study, 37 well-trained athletes (ST: 7 female, 12 male; HIIT: 9 female, 9 male) were subjected to orthostatic tests (HR and HRV recordings) each day during a 4-day baseline period, a 6-day overload microcycle, and a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 85 publications
(165 reference statements)
0
42
0
Order By: Relevance
“…This may be mitigated by optimal training, as a more pronounced decrease in parasympathetic drive (and thus possible "preservation" of orthostatic tolerance) after standing up has been observed in women with higher training volumes compared with those with lower training volumes (Gilder and Ramsbottom, 2008). There is further evidence showing that the changes in cardiac autonomic modulation during orthostatic stress may better reflect the relationship between HRV (in terms of parasympathetic responsiveness) and physical capacity and activity (Ueno and Moritani, 2003;Grant et al, 2009;Gonçalves et al, 2015), as well as exercise volume (Gilder and Ramsbottom, 2008) and training load (or overtraining) (Hynynen et al, 2008), as orthostasis may sensitively depict exercise-induced changes in cardiac autonomic modulation in response to a stimulus (Grant et al, 2012;Schneider et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be mitigated by optimal training, as a more pronounced decrease in parasympathetic drive (and thus possible "preservation" of orthostatic tolerance) after standing up has been observed in women with higher training volumes compared with those with lower training volumes (Gilder and Ramsbottom, 2008). There is further evidence showing that the changes in cardiac autonomic modulation during orthostatic stress may better reflect the relationship between HRV (in terms of parasympathetic responsiveness) and physical capacity and activity (Ueno and Moritani, 2003;Grant et al, 2009;Gonçalves et al, 2015), as well as exercise volume (Gilder and Ramsbottom, 2008) and training load (or overtraining) (Hynynen et al, 2008), as orthostasis may sensitively depict exercise-induced changes in cardiac autonomic modulation in response to a stimulus (Grant et al, 2012;Schneider et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the standing posture may add some valuable information ( Schneider et al, 2019 ), as it provokes a light and persistent (order of minutes) shift in sympathovagal balance ( Gonçalves et al, 2015 ). This autonomic shift may be influenced by training-related phenomena such as an overall vagal enhancement due to aerobic training, pre-competitive anxiety, or mere stress ( Hynynen et al, 2011 ) and fatigue carry-over from preceding exercise sessions ( Schäfer et al, 2015 ), as well as overtraining ( Hynynen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Koenig et al [12], although HRV monitoring in swimming may have some beneficial outcomes, it is also recognized that there is a lack of translational approaches to apply the current evidence to general practice. Several recent studies demonstrated the relationships between the autonomic nervous system, performance, and fatigue, showing that HRV responses appeared to depend on the training status, age, and environmental factors of the athletes [13][14][15][16][17]. However, the vastly different populations and contexts of these studies create uncertainty about the interpretation of their findings, which may partly explain why sport practitioners are still reluctant to incorporate HRV monitoring into their arsenal of training tools.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) analysis attempts to assess cardiac autonomic regulation through quantification of sinus rhythm variability. The sinus rhythm interval-time series is obtained from the QRS to QRS interval sequence of the electrocardiogram (ECG), by extracting only normal sinus to normal sinus in between two consecutive beats (9,10). High frequency alterations in sinus rhythm signifies parasympathetic modulation, while slower variations reflect a combination of both parasympathetic and sympathetic modulation and non-autonomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…High frequency alterations in sinus rhythm signifies parasympathetic modulation, while slower variations reflect a combination of both parasympathetic and sympathetic modulation and non-autonomic factors. Heart rate variability (HRV) measures are measured in two ways; time domain measures and frequency domain measures (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%